Kandungan Nitrat dan Fosfat pada Air di Sungai Telagawaja Kabupaten Karangasem, Bali - Br Sitepu, Deta Miriam; Perwira, Ima Yudha; Kartika, I Wayan Darya (Current Trends in Aquatic Science; Vol 4 No 2 (2021), 2022)
This study measured the amount of nitrates and phosphates in thewater of Telagawaja river. The water of this river is used for hygiene sanitation necessity of the people living in the surrounding area. Many antropogenic activities are exists in this area, such as: rafting and hotel, farming, and animal husbandry. This study aimed to know the status of nitrate and phosphate nutrient in the water based on the Indonesia Government Regulation Number 82 of 2001. The amount of nitrate was measured using Salifert Nitrate KIT, while phosphate was measured using Hanna HI 713 KIT. Measurement was also carried out on the total organic matter, dissolved solid, suspended solid, turbidity, dissolved oxygen, water acidity (pH), and temperature. The results showed that amount of nitrate (0.2-0.9 mg/L) and phosphate (0.1-0.4 mg/L) in the water of Telagawaja River was below the tolerance limit for all of usage class. The water of the center and the downstream might be used for fish culture, animal husbandry, irrigation water, and other usages in this standard.